Recent update on nanoemulgel as topical drug delivery system - Choudhury, Hira; Gorain, Bapi; Pandey, Manisha; Chatterjee, Lipika Alok; Sengupta, Pinaki; Das, Arindam; Molugulu, Nagashekhara; Kesharwani, Prashant (John Wiley and Sons, 2017)
Being an emerging transdermal delivery tool, nanoemulgel, has proved to show surprising upshots for the lipophilic drugs over other formulations. This lipophilic nature of majority of the newer drugs developed in this modern era resulting in poor oral bioavailability, erratic absorption, and pharmacokinetic variations. Therefore, this novel transdermal delivery system has been proved to be advantageous over other oral and topical drug delivery to avoid such disturbances. These nanoemulgels are basically oil-in-water nanoemulsions gelled with the use of some gelling agent in it. This gel phase in the formulation is nongreasy, which favors user compliance and stabilizes the formulation through reduction in surface as well as interfacial tension. Simultaneously, it can be targeted more specifically to the site of action and can avoid first-pass metabolism and relieve the user from gastric/systemic incompatibilities. This brief review is focused on nanoemulgel as a better topical drug delivery system including its components screening, formulation method, and recent pharmacokinetic and pharmacodynamic advancement in research studies carried out by the scientists all over the world. Therefore, at the end of this survey it could be inferred that nanoemulgel can be a better and effective drug delivery tool for the topical system.